Judaizers and Hebrew texts in the Court of the Inquisition of Navarre: the process of faith against Martín López (1520-1521) - de la Nogal Fernández, Rocío; del Barco del Barco, Francisco Javier (Huarte de San Juan. Geografía e Historia, 2013)
The National Historical Archive keeps a faith process of the Court of the Inquisition of Navarre inside the archive of the Inquisition Council. It is the oldest preserved. This process was initiated against Martín López in March 1520. The Court sent it to the Council in January 1521. These were complicated dates in Castile due to the revolt of the Communities, and also in Navarre, mired in the Albret dinastys attempt to regain the throne. The analyzed process is reinforced by a scroll with a medical text in Hebrew.
Keywords: Inquisition; faith process; judaizers; conquest of Navarre